De la resistencia al duelo: las ficciones sobre las dictaduras realizadas en Argentina y Chile entre 1973 y 1990 - Lusnich, Ana Laura (2014)
Allegorical and metaphorical fiction has been a highly productive tendency in Chilean and Argentinean film-making during the recent military dictatorships in both countries. The main goal of this article is to understand the dimensions and characteristics of this tendency in recent years. Its specific goals are to identify and analyse two different variants of this tendency, each of which is definable in relation to the deployment of the narrative system and the mise-en-scène; to analyse the ways in which fiction films about dictatorships sought to denounce and resist the social norms and practices instituted by the de facto governments of Argentina and Chile.